WHATSAPP MESSENGER DALAM TINJAUAN MANFAAT DAN ADAB - Jumiatmoko, Mr (Kopertais Wilayah X Jawa Tengah, 2016)
AbstractTh is study aims to determine studentsâ understanding regarding the bene? ts and Adab within the group using WhatsApp Messenger. Th is research uses descriptive quantitative approach. Th is research was conducted in Madina STIT Sragen with the subjects of the study were students of the 6th grade with total of 11 responden. Data taken with a questionnaire and analyzed using descriptive statistics. Th e results showed that 1) WhatsApp Messenger is an Instant Messaging application that its use by internetbased student Madina STIT increased from three (3) years. 2) WhatsApp Messenger makes it easy to organize various academic community-based online virtual classroom system and multimedia features without limitations of time and space. 3) WhatsApp Messenger adaptable to its social culture including adab-adab in communicating without reducing the quantity, quality and modernity of the way of communication.Keywords: WhatsApp, Benefits, Adab.